Profiles of political leaders at the local government level - Legaspi, Perla E. (Quezon City Center for Local and Regional Governance, National College of Public Administration and Governance, University of the Philippines, 2005)
"Dr. Perla E. Legaspi's "Profiles of Political Leadership at the Local Government Level" focuses on two municipal mayors, two city mayors, and two provincial governors. It sought to identify characteristics and leadership styles of local leaders and explain why they are effective and transformational leaders. The results of her study were disseminated in a seminar where there were free and open discussions on her findings."--Preface.
Part I. The study : profiles of political local government leaders -- Introduction -- Profiles of municipal leadership -- The municipal leadership of Pangil : Mayor Sergio C. Manzana -- The municipal leadership of Goa : Mayor Marcel S. Pan -- Profiles of city leadership -- The political leadership of Naga City : Mayor Jesse M. Robredo -- The political leadership of Quezon City : Mayor Feliciano F. Belmonte, Jr. -- Profiles of provincial leadership -- The provincial leadership of Nueva Vizcaya : Governor Rodolfo Q. Agbayani -- The provincial leadership of Bulacan : Governor Josefina C. Dela Cruz -- Summary and conclusions -- References -- Part II. Reactions to the study and highlights of the open forum (29 September 2005) -- Dr. Normita G. Recto -- Mayor Marcel S. Pan -- Mayor Jesse M. Robredo -- Highlights of the open forum -- Annexes.
Keywords: Local officials and employees -- Philippines; Political leadership -- Philippines; Political leaders -- Philippines